2019
DOI: 10.4103/jmp.jmp_76_18
|View full text |Cite
|
Sign up to set email alerts
|

Validation of three-dimensional electronic portal imaging device-based PerFRACTION™ software for patient-specific quality assurance

Abstract: Purpose: PerFRACTION™ is a three-dimensional (3D) in vivo electronic portal imaging device-based dosimetry software. To validate the software, three phantoms with different inserts (2D array, ionization chamber, and inhomogeneity materials) were constructed to evaluate point dose and fluence map. Materials and Methods: Phantoms underwent independent computed tomography simulation for planning and received repetitive fractions of volumetric mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Sait et al [22] found that the estimation of point dose calculated by using machine log file in PerFRACTION, is in agreement with measurements using an ionization chamber; similar results were observed in…”
Section: Discussionsupporting
confidence: 67%
“…Sait et al [22] found that the estimation of point dose calculated by using machine log file in PerFRACTION, is in agreement with measurements using an ionization chamber; similar results were observed in…”
Section: Discussionsupporting
confidence: 67%
“…For example, linac log files can be used as input for independent dose verification 56 . Alternatively, measured fluences with an EPID or a transmission detector can be used as input data for independent dose calculation 57‐59 …”
Section: Role Of Dose/mu Verifications In a Comprehensive Qa Programmentioning
confidence: 99%
“…56 Alternatively, measured fluences with an EPID or a transmission detector can be used as input data for independent dose calculation. [57][58][59]…”
Section: Statement Of the Problem And Tg Chargesmentioning
confidence: 99%
“…Esposito et al 18 presented the validation of a back-projection software with slab and anthropomorphic phantoms. Previous works 69,70 also had validated the PerFRACTION collapsed-cone convolution/superposition algorithm with experimental measurements performed with ionization chambers and detector arrays. However, in all these works, the calculated dose and the measurements were performed at the patient level.In a forward-projection transit dosimetry software, the transit image is calculated under different conditions, as it is obtained after the patient at the EPID level and not in the patient.…”
Section: Discussionmentioning
confidence: 99%
“… 18 presented the validation of a back‐projection software with slab and anthropomorphic phantoms. Previous works 69 , 70 also had validated the PerFRACTION collapsed‐cone convolution/superposition algorithm with experimental measurements performed with ionization chambers and detector arrays. However, in all these works, the calculated dose and the measurements were performed at the patient level.…”
Section: Discussionmentioning
confidence: 99%